2016
DOI: 10.1080/15398285.2016.1167580
|View full text |Cite
|
Sign up to set email alerts
|

The Health-Related Uses and Gratifications of YouTube: Motive, Cognitive Involvement, Online Activity, and Sense of Empowerment

Abstract: AND SENSE OF EMPOWERMENTThe purpose of this study was to examine the relationships among motives for health-related YouTube use, cognitive involvement with health information on YouTube, post-exposure online activity, and sense of empowerment regarding health and health care. As a result of the analysis of data from 263 participants, social utility, convenient information-seeking, habit-passing time, and exciting entertainment motives were identified as four motives for health-related YouTube use. Social utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 54 publications
(117 reference statements)
2
20
0
Order By: Relevance
“…Banerjee & Dholakia (2008), suggest that the more relevant a message is perceived by the consumer, the easier it is to process due to the activation of familiar knowledge, thus enhancing its appeal. Moreover, it has been found that the more involved the consumer is regarding the subject of the communication, the more likely they are to attend to it (Park & Goering, 2016). For example, tourist recommendations systems that are effectively using customer profiles can recommend relevant points of interest to improve trip experiences (Wang et al, 2016).…”
Section: The Personalisation Benefitsmentioning
confidence: 99%
“…Banerjee & Dholakia (2008), suggest that the more relevant a message is perceived by the consumer, the easier it is to process due to the activation of familiar knowledge, thus enhancing its appeal. Moreover, it has been found that the more involved the consumer is regarding the subject of the communication, the more likely they are to attend to it (Park & Goering, 2016). For example, tourist recommendations systems that are effectively using customer profiles can recommend relevant points of interest to improve trip experiences (Wang et al, 2016).…”
Section: The Personalisation Benefitsmentioning
confidence: 99%
“…The UG literature states that individuals contrast in their media use as they vary in their requirements for media utilization, and it is likely that there are particular purposes behind users with well-being-related worries to use YouTube ( Park & Goering, 2016 ). The gratifications sought in YouTube use are numerous and include elements of both conventional media and those of social networking.…”
Section: Youtube Uses and Gratificationsmentioning
confidence: 99%
“…Users tend to expect functional or psychological gratifications from YouTube content. For example, Park and Goering ( 2016 ) attributed YouTube as a health-related companion in their study. Websites like Facebook and other social media platforms largely acquire unplanned traffic.…”
Section: Youtube Content Viewing and Content Creation Inclinmentioning
confidence: 99%
“…The results of the present study, namely the fact that 100% of the videos are directed towards the general population rather than professionals, suggest that YouTube constitutes a space where medical information, including highly specialized procedures such as the application of Botox, is discussed directly with users, often bypassing expert advice and fulfilling the motivations of users to consume health information on YouTube [ 28 ]. Although the sampling criteria excluded videos created by professionals, it is relevant to mention that user-generated content related to Botox application is aimed at the general population rather than professionals, because it supports previous research as explained above and sets the stage for the analysis of the relationship-establishing strategies that respond to RQ1.…”
Section: Discussionmentioning
confidence: 99%